Constitutional law of the European Union - Lenaerts, Koenraad; Van Nuffel, Piet; Bray, Robert (London : Thomson/Sweet & Maxwell, 2006)
"This book presents the constitutional law of the European Union in the broadest sense of the expression. It provides a systematic exposition of the Union's competences, procedures and instruments while raising the issues which lawyers are likely to encounter in practice." "With its multiple references to Internet sites and doctrinal articles in various languages, the book aims to be a tool for practitioners, academics and students world-wide."--BOOK JACKET.
The European Union: different paths toward integration -- Jurisdiction of the European Union -- The actors of the European Union -- The decision-making process within the European Union -- Sources of law of the European Union -- The external relations of the European Union.
BIBINDX
Translation of the rev. ed. of Europees recht in hoofdlijnen.
Keywords: European Union; Constitutional law -- European Union countries